Uglies - Westerfeld, Scott (New York : Simon Pulse, 2005)
Just before their sixteenth birthdays, when they will will be transformed into beauties whose only job is to have a great time, Tally's best friend runs away and Tally must find her and turn her in, or never become pretty at all.
Sequel: Pretties.
Keywords: Beauty, Personal -- Juvenile fiction; Teenage girls -- Juvenile fiction; Young adult fiction